Usability and reliability of remote autism diagnostic observation schedule (ADOS) module 4 administration - Schutte, Jamie Lynn (ProQuest Dissertations & Theses, 2012)
Autism Spectrum Disorder (ASD) is characterized by impairments in social interaction, impairments in communication, and restricted repetitive and stereotyped patterns of behavior, interests, and activities. The Autism Diagnostic Observation Schedule (ADOS) Module 4 is a semi-structured diagnostic assessment tool designed for verbally fluent adolescents and adults with possible ASD. Due to a lack of available clinical expertise, it can be difficult for adults to receive an accurate ASD diagnostic assessment, especially those residing in rural areas. An ADOS teleassessment system was developed using the Versatile and Integrated System for Telerehabilitation (VISYTER). VISYTER consists of computer stations at the client site and clinician site, and a web portal server for managing and coordinating all elements of the assessment process. Clinician usability and fidelity to standard, face-to-face administration, was assessed. After improvements to the system were made, a study was conducted to determine the reliability of the ADOS module 4 administrations delivered remotely. Twenty-three adults with an ASD diagnosis participated in a within-subject crossover design study in which both a remote and face-to-face ADOS were administered. Weighted kappa was calculated for all 31 ADOS items. There was substantial agreement on 11 items and almost perfect or perfect agreement on 10 items. Intraclass correlations (ICCs) were calculated for algorithm subtotals. ICCs were greater than .75 for three out of four subtotals. There was substantial agreement on ADOS classification (i.e., diagnosis) between assessments delivered face-to-face versus assessments delivered remotely, Po=83%; K =.772, ICC=.92. Non-agreement may have been due to outside factors or practice effect despite a washout period. Finally, usability and satisfaction of the remote assessment system was evaluated from the participants' perspectives. Participant satisfaction with the remote ADOS delivery system was high. The results of these studies demonstrate that an ASD assessment designed to be delivered face-to-face can be reliably administered remotely using an integrated web-based system.